Temporal and Spatial Evolution of Chinese Museums and Their Causes Analysis - Liu Hailong; Liu Meitong; Hu Xuhong; Guo Xiaojia (Redai dili, 2022)
With the transformation and development of China's economy and society, the state attaches great importance to the equalization of public services to meet the growing demand for a better life. Museums are not only one of the most important needs of people's spiritual culture but are also an important part of the public cultural service system. Their reasonable layout has an important impact on the equalization of basic public services. Therefore, research on the temporal and spatial evolution of museums has become one of the hotspots of related disciplines, and is of great significance to deepen the basic public service theory. This study selects a list of museums from 1990 to 2018 and uses a nuclear density analysis, standard deviation ellipse, spatial autocorrelation, and geographic detector model, to analyze the evolution trend of museum quantity, evolution characteristics of spatial distribution mode, law of spatial differentiation, and influencing factors of the temporal and spatial distribution of the museums. The results show that: 1) in terms of quantity evolution trend, there are significant differences in the number of museums from 1990-2000, 2000-2010, and 2010-2018, with a gradual increase in the number. Overall, the number of museums showed an accelerated growth trend from 1990-2018. The differences between the East and West are obvious. The number of museums in the eastern region is dense and the development is rapid; contrastingly, the number of museums in the central and western regions is sparse and development is relatively slow. 2) In terms of the evolution of spatial distribution mode, over time, Chinese museums continue to gather spatially and gradually evolve from "single center" distribution mode to "multi center" distribution mode, and the degree of agglomeration continues to improve. 3) The standard deviation ellipse analysis shows that from 1990-2018, the center of gravity of the Chinese museums was always located in the East; the center of gravity shifted slightly over time, and the moving track was about "Z." 4) In terms of the spatial differentiation law, there has been a significant spatial agglomeration process of Chinese museums since 1990, forming a pattern of "hot in the East and cold in the west". The middle and lower reaches of the Yangtze River are the hotspots of Chinese museums, and Xinjiang and Tibet are always in the cold spots. Additionally, the scope of hotspots continues to expand annually, extending to the northwest inland, which is consistent with China's strategy of "equalization of public cultural services" in recent years; it is also conducive to breaking the layout of public cultural facilities that are "strong in the East and weak in the West." 5) In terms of influencing factors, museum spatial differentiation is the result of the comprehensive action of multiple factors, which is mainly affected by the economy, society, policy, culture, and education. Among them, policy, cultural, and educational factors are the main influencing factors of museum spatial differentiation, followed by social factors, and economic factors are the general factors affecting its distribution.